2021
DOI: 10.1108/ribs-07-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of influencers’ credibility dimensions: attractiveness, trustworthiness and expertise on the purchase intention in the aesthetic dermatology industry

Abstract: Purpose This study aims to investigate the influencers’ credibility dimensions (i.e. attractiveness, trustworthiness, expertise) on purchase intention (PI) through the mediating role of cognitive and affective online engagement among the aesthetic dermatology consumers in Jordan. Design/methodology/approach The population of this study entails all followers of aesthetic dermatology clinics on their Instagram accounts. However, only three influencers from the aesthetic dermatology industry were selected and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 50 publications
7
63
1
4
Order By: Relevance
“…Regarding digital influencers, attractiveness was identified as one of the relevant attributes that influences elements such as brand image, brand satisfaction, brand trust, and purchase intention [39]. In addition, attractiveness has an impact on online engagement and purchase intention [58] and positively predicts attitudes toward the influencer, wordof-mouth, and purchase intentions [14]. Moreover, Liu et al [59] found that attractiveness is indeed an important factor affecting consumers' purchase intention.…”
Section: Attractivenessmentioning
confidence: 99%
“…Regarding digital influencers, attractiveness was identified as one of the relevant attributes that influences elements such as brand image, brand satisfaction, brand trust, and purchase intention [39]. In addition, attractiveness has an impact on online engagement and purchase intention [58] and positively predicts attitudes toward the influencer, wordof-mouth, and purchase intentions [14]. Moreover, Liu et al [59] found that attractiveness is indeed an important factor affecting consumers' purchase intention.…”
Section: Attractivenessmentioning
confidence: 99%
“…Attractiveness is one of the three core constructs of influencer credibility, along with expertise and trustworthiness (AlFarraj et al, 2021;Chekima, Chekima and Adis, 2020). Using influencer attractiveness can serve as an important reference for brands to communicate with their potential customers (Chekima et al, 2020).…”
Section: Influencer Attractivenessmentioning
confidence: 99%
“…Using influencer attractiveness can serve as an important reference for brands to communicate with their potential customers (Chekima et al, 2020). Influencer attractiveness is not only related to the physical characteristics of a particular influencer but also to the admiration, personality and athletic ability of that influencer (AlFarraj et al, 2021;Torres et al, 2019). The use of social media-based influencer marketing is important to build relationships between consumers and brands (Glucksman, 2017).…”
Section: Influencer Attractivenessmentioning
confidence: 99%
“…Kecantikan dan pengetahuan mempengaruhi keterlibatan online dan nilai pembelian. Selanjutnya, ditemukan bahwa keterlibatan online memiliki efek mediasi pada hubungan antara kredibilitas influencer dan niat membeli (AlFarraj et al, 2021). Dengan merek yang sudah dikenal, pengaruh kesesuaian jenis endorser dan daya tarik pesan terhadap persepsi merek lebih besar dibandingkan dengan perusahaan baru.…”
Section: Gambar 3 Aktivitas Pengguna Instagramunclassified